Agrobacterium-mediated direct transformation of wheat mature embryos through organogenesis - Ye, Xudong; Shrawat, Ashok; Moeller, Lorena; Rode, Rebecca; Rivlin, Anatoly; Kelm, David; Martinell, Brian J.; Williams, Edward J.; Paisley, Anthony; Duncan, David R.; Armstrong, Charles L. (Frontiers in Plant Science, 2023)
Transgenic plant production in monocotyledonous species has primarily relied on embryogenic callus induction from both immature and mature embryos as the pathway for plant regeneration. We have efficiently regenerated fertile transgenic wheat plants through organogenesis after Agrobacterium-mediated direct transformation of mechanically isolated mature embryos from field-grown seed. Centrifugation of the mature embryos in the presence of Agrobacterium was found to be essential for efficient T-DNA delivery to the relevant regenerable cells. The inoculated mature embryos formed multiple buds/shoots on high-cytokinin medium, which directly regenerated into transgenic shoots on hormone-free medium containing glyphosate for selection. Rooted transgenic plantlets were obtained within 10-12 weeks after inoculation. Further optimization of this transformation protocol resulted in significant reduction of chimeric plants to below 5%, as indicated by leaf GUS staining and T1 transgene segregation analysis. Direct transformation of wheat mature embryos has substantial advantages over traditional immature embryo-based transformation systems, including long-term storability of the mature dry explants, scalability, and greatly improved flexibility and consistency in transformation experiments.